42.0k views
2 votes
Using substitution to solve the system below, what expression should be substituted into the first equation? 2x-4y=-4 and x+2y=8

User Pablote
by
5.7k points

2 Answers

3 votes

Answer:


Explanation:

Choices?

User Dudewad
by
5.5k points
1 vote

Answer:

Given the system of equation:


2x-4y=-4 ......[1]


x+2y=8 ......[2]

we can rewrite equation [2] as;


x = 8-2y ......[3]

Substitute equation [3] into [1] to eliminate x, and solve for y;


2(8-2y)-4y = -4

Using distributive property:
a\cdot (b+c) = a\cdot b+ a\cdot c


16-4y -4y = -4

Combine like terms;

16 - 8y = -4

Add 4 to both sides we have;

20 - 8y = 0

Add 8y to both sides we have;

20 = 8y

Divide 8 to both sides we have;


y = 2.5

Substitute the y-value in [3] we have;


x = 8-2(2.5)

x = 8 - 5 = 3

Therefore, the expression should be substituted into the first equation is,
x = 8-2y and also the value of x = 3 and y = 2.5

User Mmatyas
by
5.4k points